1995
DOI: 10.1136/fn.72.1.f23
|View full text |Cite
|
Sign up to set email alerts
|

Essential fatty acids in full term infants fed breast milk or formula.

Abstract: To determine the biochemical effects of the fatty acid composition of plasma lipids, two groups of 10 healthy full term infants who were either exclusively breast fed or received a formula with similar contents of linoleic and a. linolenic acids, but without long chain polyunsaturated (LCP) fatty acids, were studied prospectively. Plasma phospholipid, triglyceride, and sterol ester fatty acids were determined at the age of 2, 4, and 8 weeks by high resolution capillary gas chromatography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 35 publications
(10 reference statements)
3
26
0
Order By: Relevance
“…Studies assessing the relationship between brain fatty acids and diet in infancy have demonstrated that breast-fed infants have higher concentrations of DHA in their cerebral cortex compared with infants fed formula without AA and DHA (Farquharson et al, 1992;1995), but there were no differences in the level of AA. Makrides et al, (1994) and Decsi et al, (1995) observed that infants fed with formula without AA and DHA develop AA and DHA depletion of structural lipids.…”
Section: Fatty Acid Composition Of Infant Formulasmentioning
confidence: 99%
“…Studies assessing the relationship between brain fatty acids and diet in infancy have demonstrated that breast-fed infants have higher concentrations of DHA in their cerebral cortex compared with infants fed formula without AA and DHA (Farquharson et al, 1992;1995), but there were no differences in the level of AA. Makrides et al, (1994) and Decsi et al, (1995) observed that infants fed with formula without AA and DHA develop AA and DHA depletion of structural lipids.…”
Section: Fatty Acid Composition Of Infant Formulasmentioning
confidence: 99%
“…This was followed by measurement of a variety of reflex and sensorimotor functions, including tactile responsiveness, postural adjustment capabilities, and muscle tone. In addition, the response to a brief challenge was assessed during a 6-min session in which the animal was placed into a small cage (see above for description of the housing cage used during d [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. The test cage was empty except for an absorbent liner pad and the stimulus used for the visual orienting items.…”
Section: Neonatal Assessmentmentioning
confidence: 99%
“…In contrast to human milk, commercial infant formulas until recently did not contain LCPUFA (Koletzko & Bremer, 1989). Term and particularly preterm infants, fed formulas that contain linoleic acid and a-linolenic acid but are devoid of LCPUFA, develop LCPUFA depletion of structural lipids, as measured by plasma and erythrocyte membrane concentrations (Putnam et al 1982;Koletzko et al 1989;Makrides et al 1994;Decsi et al 1995). Studies assessing the relationship between brain fatty acids and diet in infancy have demonstrated that breast fed infants have higher concentrations of DHA in their cerebral cortex compared with infants fed formula milk (Farquharson et al 1992(Farquharson et al , 1995Makrides et al 1994).…”
Section: Lcpufa Supplementation For Term Infants?mentioning
confidence: 99%